STUDI ETNOGRAFI PERILAKU SOSIAL ANAK DI PULAU SEBESI LAMPUNG - Kurniasih, Siti; Tejapermana, Prisma (Jurnal Caksana : Pendidikan Anak Usia Dini, 2018)
This study describes the social behavior of childhood at Sebesi Island South Lampung, Lampung Province in 2018. This study used a qualitative research with ethnographic methods. The data were collected through observation, interview, photo documentation, and written documentation. The data were analyzed by Spradley models. The result showed that (1) Social behavior of early childhood at the Sebesi Island is formed in traditions of activities together that followed by early childhood (2) The process of formation of social behavior in early childhood through the direct involvement of children by following the traditions (3) the involvement of the community (socio-cultural) through all citizens participation and communities in providing direct example through traditional activity. The recommendations of this study are a reflection of social behavior in early childhood, especially in society life and multicultural education. Keywords: social behavior, early childhood, ethography